2005
DOI: 10.1142/s0192415x05002783
|View full text |Cite
|
Sign up to set email alerts
|

The Antimicrobial Activities of Psidium guajava and Juglans regia Leaf Extracts to Acne-Developing Organisms

Abstract: This study aims to present the in vitro inhibitory effect of Psidium guajava and Juglans regia leaf extracts on the main developer of acne lesions, Propionibacterium acnes (P. acnes), and other organisms that are isolated from acne lesions. Thirty-eight subjects (males and females) who had various types of acne were enrolled in the study. The contents of the acne lesions were cultured and the frequency of P. acnes (alone and with Staphylococci spp.) was 47%, whereas the frequencies for Staphylococcus aureus an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
60
1
4

Year Published

2006
2006
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(68 citation statements)
references
References 13 publications
3
60
1
4
Order By: Relevance
“…This could provide an explanation for our results [10,21]. Inhibitory effects of acetone leaf extracts showed similar results to those of other studies [6,10,22].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This could provide an explanation for our results [10,21]. Inhibitory effects of acetone leaf extracts showed similar results to those of other studies [6,10,22].…”
Section: Discussionsupporting
confidence: 92%
“…Psidium guajava juice has also been used as a hypoglycemic agent [4]. Studies on the antimicrobial effect of guava have been carried mainly on extracts of leaves, shoots and barks, as well as seeds [5,6,7,8,9]such extracts have also been found to inhibit the growth of drug resistant microbes such as V. cholera [10]and to act synergistically with existing antibiotics to treat the pathogenic Staphylococcus aureus [11]as well as other food pathogens [5,6,7,11,12], or in improving oral hygiene and inhibiting biofilm formation by Streptococcus mutant [13].…”
Section: Introductionmentioning
confidence: 99%
“…In vitro studies on plants used in traditional medicine have been carried out in the field of microbiology, especially on pathogenic bacterial growth; and some of these studies were about the antimicrobial activity of Mikania glomerata Spreng ("guaco") (Boyayan 2002, Holetz et al 2002, Psidium guajava L (guava) (Gnan & Demello 1999, Jaiarj et al 1999, Nascimento et al 2000, Ahmad & Beg 2001, Abdelrahim et al 2002, Holetz et al 2002, Voravuthikunchai et al 2004, Qadan et al 2005, Syzygium …”
mentioning
confidence: 99%
“…In vitro studies on plants used in traditional medicine have been carried out in the field of microbiology, especially on pathogenic bacterial growth; and some of these studies were about the antimicrobial activity of Mikania glomerata Spreng ("guaco") (Boyayan 2002, Holetz et al 2002, Psidium guajava L (guava) (Gnan & Demello 1999, Jaiarj et al 1999, Nascimento et al 2000, Ahmad & Beg 2001, Abdelrahim et al 2002, Holetz et al 2002, Voravuthikunchai et al 2004, Qadan et al 2005 (Ankri & Mirelman 1999, Ahmad & Beg 2000, Srinivasan et al 2001, Benkeblia 2004, Zingiber officinale Roscoe (ginger) (Silva Junior et al 1994, Konning et al 2004, Cymbopogon citratus (DC) Stapf (lemongrass) (Cimanga et al 2002, Di Stasi & HirumaLima 2002, Mentha piperita L (mint) (Silva Junior et al 1994, Tassou et al 2000, and Baccharis trimera (Less.) DC ("carqueja") (Avancini et al 2000).…”
mentioning
confidence: 99%
“…Leaf extract of the walnut showed, J. regia L., showed that they both had contact and systemic toxicity acaricidal activity on the mites Tetranychus cinnabarinus (Boisduval) and Tetranychusviennensis Zacher (Acari: Tetranychidae) [40]. J. regia leaves composed of terpenes, hydrocarbons, esters, flavonoids and phenolic compounds [41]. It was revealed that phenolic compounds such as tannins, flavanols and flavonoids were toxic to bacteria, fungi and insects [42].…”
Section: Effect On Egg Laying Capacitymentioning
confidence: 99%